6 DOF calibration of profile sensor locations in an inspection station. Issue 1 (2020) - Morse, Edward; Jaganmohan, Prashanth
Abstract: Traditional coordinate measuring systems rely on the accurate kinematics of moving a sensor to the workpiece. This paper describes an instrument using a precision rotary stage to rotate a workpiece with respect to a set of three laser line sensors. The accuracy of the point cloud obtained from a single rotation of the workpiece is dependent on the rotational accuracy of the stage and knowledge of the location of the line sensors with respect to the rotary axis and each other. The calibration procedure required to locate these line sensors utilizes a precision artefact placed on the rotary stage.